The Changing Trends of West Sumatera Youth Political Participation in the West Sumatra Governor Election 2020 - Najmuddin Mohammad Rasul (International Journal of Media and Communication Research, 2021)
This survey aims to see the relationship between the media and changes in the norm of citizenship and the political participation of young voters in the West Sumatra Governor Election on December 9, 2020. This survey uses the survey method with 350 respondents in West Sumatra. The survey results show that the differences in gender, age and educational background of respondents do not significantly affect the media and changes in citizenship norms. The results of the hypothesis testing that have been carried out show that educational background is not a differentiating factor for the media, but a differentiating factor for changes in citizenship norms. Furthermore, the relationship analysis test shows that often the media has a significant relationship with changes in citizenship norms. Meanwhile, citizenship norms have a significant relationship with citizens' political participation. Then, the regression analysis test found that media and changes in citizenship norms together make a significant contribution to political participation. Based on the results of the survey and the results of hypothesis testing, it can be concluded that political euphoria in the transition to democracy has changed media patterns, citizenship norms, and political participation among young voters in West Sumatra.